2018
DOI: 10.1177/0091450918782493
|View full text |Cite
|
Sign up to set email alerts
|

Balancing Between Hope and Realism

Abstract: Pregnancy for women who use substances has sometimes been referred to as a "window of opportunity" for lifestyle change. In this article, the aim is to analyze professional accounts of the transition of substance-using pregnant women into parenthood. Focus groups were carried out with professionals working at specialized maternity care units in Sweden. The analysis is guided by the discursive psychological concept of "ideological dilemma" and focuses on contradictory elements of commonsensemaking in the partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Provider-focused studies highlight the strong concerns providers hold regarding child safety and their perceptions of mothers with an SEP as "risky" (Fraser et al, 2007;Maguire et al, 2012;Murphy-Oikonen et al, 2010;Shaw et al, 2016, Whittaker et al, 2019. When met with resistance from women with an SEP, healthcare providers have expressed difficulty in carrying out their professional obligations (Heimdahl, 2018). These tensions can impair healthcare and other service providers' ability to separate their emotions from decision-making in treatment to meet the needs of women with an SEP (Heimdahl, 2018;Miles et al, 2014).…”
Section: Provider Perceptions Of Perinatal Substance Usementioning
confidence: 99%
See 1 more Smart Citation
“…Provider-focused studies highlight the strong concerns providers hold regarding child safety and their perceptions of mothers with an SEP as "risky" (Fraser et al, 2007;Maguire et al, 2012;Murphy-Oikonen et al, 2010;Shaw et al, 2016, Whittaker et al, 2019. When met with resistance from women with an SEP, healthcare providers have expressed difficulty in carrying out their professional obligations (Heimdahl, 2018). These tensions can impair healthcare and other service providers' ability to separate their emotions from decision-making in treatment to meet the needs of women with an SEP (Heimdahl, 2018;Miles et al, 2014).…”
Section: Provider Perceptions Of Perinatal Substance Usementioning
confidence: 99%
“…When met with resistance from women with an SEP, healthcare providers have expressed difficulty in carrying out their professional obligations (Heimdahl, 2018). These tensions can impair healthcare and other service providers' ability to separate their emotions from decision-making in treatment to meet the needs of women with an SEP (Heimdahl, 2018;Miles et al, 2014). While many providers report empathy for mothers and understand the complexity of their situation, they still struggle with their own biases and judgmental thoughts (Benoit et al, 2014;Geraghty et al, 2019).…”
Section: Provider Perceptions Of Perinatal Substance Usementioning
confidence: 99%
“…In family treatment settings, parenthood is the focus of change and is thus constructed in relation to professionals who may have negative attitudes towards substance abusers. This may affect how treatment-seeking parents understand themselves and how they identify with their parental roles (Grunow & Evertsson, 2021; Heimdahl, 2018; Lind et al, 2017). In the research by Virokannas (2011), drug-abusing mothers experienced the role of welfare authorities mostly as adversaries and only seldom as a partnership, while in the study by Chou et al (2020) mothers found support from personnel important.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In families with parental substance abuse, the special needs of parents and children are often interconnected (Akin et al, 2015;Alexanderson & Näsman, 2017). Effective support for parenthood in addiction treatment and family-focused treatment can strengthen parenting skills and parents' emotional coping, which may help them in parenting and also lead to better outcomes for people abusing intoxicants (e.g., Dawe et al, 2021;Heimdahl, 2018;Neger & Prinz, 2015;Seay et al, 2017).…”
mentioning
confidence: 99%